Metabolic Syndrome and Side Effects of Atypical Antipsychotics in Schizophrenia: A Literature Review - Andinny Nur Permatasari; Yulistiani (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2025)
Atypical or second-generation antipsychotics are the most frequently prescribed antipsychotics due to their clinical efficacy and improved safety profile in the treatment of schizophrenia when compared to typical or first-generation antipsychotics. However, atypical antipsychotic drugs are associated with a high prevalence of adverse reactions, as well as side effects of metabolic syndrome. Schizophrenia is a chronic mental illness characterized by positive, negative, and cognitive dysfunctions. The objective of this review is to compare the impacts of atypical medication on MetS in patients with schizophrenia. A comprehensive analysis was conducted, including a literature review of the databases of Google Scholar, PubMed, and ScienceDirect for publications over the past decade. Seven articles were selected and reviewed for analysis. The analysis revealed that the use of atypical antipsychotics was associated with an increased risk of metabolic syndrome, while clozapine, olanzapine, and risperidone were associated with a higher risk of metabolic syndrome compared to other antipsychotics. The study also explores the mechanisms of metabolic syndrome, with a specific focus on the role of antipsychotics in disrupting glucose and lipid metabolism. This comprehensive study offers a nuanced understanding of the adverse effects of antipsychotic medications on the development of metabolic syndrome in individuals diagnosed with schizophrenia. This review revealed that the use of atypical antipsychotics in the treatment of schizophrenia can increase the risk of metabolic syndromes such as weight gain, dyslipidemia, hypertension, and diabetes. The primary limitation of this review is the high heterogeneity among studies, as they employed varying definitions of metabolic syndrome and included diverse sample characteristics.